[download] (2154)The RcmdrPlugin.survival Package: Extending the R Commander Interface to Survival Analysis - John Fox; Marilia Sa Carvalho (Journal of Statistical Software, 2012)
The R Commander graphical user interface to R is extensible via plug-in packages, which integrate seamlessly with the R Commander's menu structure, data, and model handling. The paper describes the RcmdrPlugin.survival package, which makes many of the facilities of the survival package for R available through the R Commander, including Cox and parametric survival models. We explain the structure, capabilities, and limitations of this plug-in package and illustrate its use.